The Function of Root Exudates in the Root Colonization by Beneficial Soil Rhizobacteria - Lin Chen; Yunpeng Liu (Biology, 2024)
Soil-beneficial microbes in the rhizosphere play important roles in improving plant growth and health. Root exudates play key roles in plant–microbe interactions and rhizobacterial colonization. This review describes the factors influencing the dynamic interactions between root exudates and the soil microbiome in the rhizosphere, including plant genotype, plant development, and environmental abiotic and biotic factors. We also discuss the roles of specific metabolic mechanisms, regulators, and signals of beneficial soil bacteria in terms of colonization ability. We highlight the latest research progress on the roles of root exudates in regulating beneficial rhizobacterial colonization. Organic acids, amino acids, sugars, sugar alcohols, flavonoids, phenolic compounds, volatiles, and other secondary metabolites are discussed in detail. Finally, we propose future research objectives that will help us better understand the role of root exudates in root colonization by rhizobacteria and promote the sustainable development of agriculture and forestry.